2018
DOI: 10.1002/cbic.201800393
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Spectroscopic Insight into the Supramolecular Interactions in DNA‐Based Enantioselective Sulfoxidation

Abstract: Interactions of copper(II)-bipyridine cofactors and thioanisole substrate with human telomeric G-quadruplex DNA were studied by UV/Vis absorption, circular dichroism, and fluorescence quenching titration. Three copper(II)-bipyridine complexes are equivalently anchored to the G-quadruplex scaffold at all five fluorescently labeled sites. Thioanisole interacts with the DNA architecture at both the second loop and 3' terminus in the absence or presence of copper(II)-bipyridine complexes. These nonspecificities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 84 publications
2
10
0
Order By: Relevance
“…of 21 % and À 46 %, respectively (Table 1). This observation is consistent with that of Can Li group [38] because, in the case of mimic 2, the RAFT crowds the two areas of substrate interaction with the G-4 identified (Figure 1), demonstrating that asymmetric induction occurs where the contact is stronger. [38]…”
Section: Sulfoxidation With the Antiparallel Mimicsupporting
confidence: 88%
See 2 more Smart Citations
“…of 21 % and À 46 %, respectively (Table 1). This observation is consistent with that of Can Li group [38] because, in the case of mimic 2, the RAFT crowds the two areas of substrate interaction with the G-4 identified (Figure 1), demonstrating that asymmetric induction occurs where the contact is stronger. [38]…”
Section: Sulfoxidation With the Antiparallel Mimicsupporting
confidence: 88%
“…Our findings for antiparallel and, by extension, hybrid native G-4 corroborate that the reaction occurs at the 3'-tetrad and/or the L2 loop in the case of HT21. [38] Finally, since the reaction can occur at different sites and topologies, constrained G-4 provides a versatile platform for asymmetric sulfoxidation as well as hints about how the process works.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11] Catalytic DNA usually comprises a sequence in which a tertiary structure is encoded which, upon interaction with a metal cofactor, 12 accelerates chemical reactions. [13][14][15][16][17][18][19][20][21] An interesting tertiary structure is the G-quadruplex (GQ) that folds from guanine-rich sequences through the stacking of G-quartets, i.e., arrays of four guanines associated via Hoogsteen hydrogen bonds. [22][23][24][25][26] A GQ exhibits enticing catalytic properties notably upon interaction with hemin (Fe(III)-protoporphyrin IX), a well-known cofactor of hemoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…The best effects of asymmetric induction (up to 97% ee ) were also achieved in the category of copper-Schiff base catalysts described by Maguire and co-workers . The first use of nucleic acid-bound copper­(II) complex with bipyridine in sulfoxidation of thioanisole by aqueous hydrogen peroxide was reported by Cheng et al , A transfer of chirality for G-quadruplex DNA to the product was observed with the enantiomeric excess up to 56% (99% conversion). CD and fluorescence quenching measurements showed that the limited stereoselectivity may result from relatively weak, nonspecific interactions of both thioanisole and Cu complexes with the quadruplex.…”
Section: Preparation Of Chiral Nonracemic Sulfoxidesmentioning
confidence: 99%